"Age estimation and sex determination using antegonial angle–A retrospective study". (March 2023) - Anuja, P.; Doggalli, Nagabhushana; Patil, Karthikeya; Johnson, Abraham; Manjunatha, Bhari S.; Rudraswamy, Sushma
Highlights : To assess the values of the antegonial angle on panoramic radiographs. Assess their role in age and sex determination. This study showed that the antegonial angle is influenced by sex but not by age. Antegonial angle can be used as a forensic tool for sex determination. Not a reliable parameter for the estimation of age. Abstract: Objective: To assess the values of the antegonial angle on panoramic radiographs and assess their role in age and sex determination. Materials & Method: A study was carried out on 400 selected panoramic radiographs (200 males and 200 females) in the age group of 20 to 70 years. The antegonial angle was evaluated for its predictability in sex determination and age assessment. Required Statistical analysis was done. Results: There was a significant difference in mean values of antegonial angle between males and females. Conclusion: The antegonial region values are influenced by sex and have the potential to be used as a forensic tool in sex determination but not for age estimation. Graphical abstract: Image, graphical abstract